Examination of mental toughness, anxiety, and Generalized Anxiety Disorder-7 (GAD-7) levels of elite and amateur cyclists - Aslan, S.; Agbuga, B. (Turkish Journal of Sport and Exercise, 2025)
Nowadays, it is an accepted fact that in order to achieve high performance in sports environment, the athlete's psychological competence is as important as his/her physical competence. Cycling is an activity performed by large masses all over the world for recreational, health, and performance purposes. This study aims to examine some psychological variables (mental toughness, anxiety and worry, and Generalized Anxiety Disorder levels) of amateur and elite cyclists. The sample of the study consisted of 124 amateur and 95 elite volunteer cyclists between the ages of 15-41 (N=219) who cycle throughout Turkey. Personal information form, Mental Toughness Scale, Worry and Anxiety Scale, and Generalized Anxiety Scale-7 prepared considering the DSM-IV SCID-I clinical interview guide were used as data collection tools in the study. Independent t-test and ANOVA statistical analyses were used in the analysis of the study. As a result of the analyses, (1) men's mental toughness levels were found to be higher than women's, but there was no significant difference between them (p>0.05). (2) It was found that women's levels of worry and anxiety and generalized anxiety disorder were higher than men's (p<0.001). (3) Elite cyclists' mental toughness levels were found to be higher than amateurs (p<0.05). (4) Amateur cyclists' worry and anxiety levels were higher than elite cyclists' (p<0.005). (5) Cyclists' mental toughness levels were high, while worry and anxiety, and generalized anxiety disorder levels were moderate. As a result, this study shows that the levels of mental toughness, anxiety and generalized anxiety disorder of cyclists may vary depending on gender, age and sport level (amateur/elite).